2015
DOI: 10.1162/ajhe_a_00028
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Insurance on HIV Testing

Abstract: ne e r aj s o o d z achary wagn er ya n y u wu A B S T R A C T This paper investigates the effects of health insurance on HIV testing rates among the US general population using nationally representative data from the Behavioral Risk Factor Surveillance Survey (BRFSS) for the years 1993 to 2003. We estimate recursive bivariate probit models with insurance coverage and HIV testing as the dependent variables. We use changes in Medicaid eligibility and distribution of firm size over time within a state as instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Our finding also highlights the significance of health care coverage to uptake of HIV testing in the United States. 49 HIV testing for pregnant women has been recommended by the United States Preventive Services Task Force as grade ‘A’ preventive service, and hence it is provided by most insurers without cost-sharing under the Affordable Care Act. 50…”
Section: Discussionmentioning
confidence: 99%
“…Our finding also highlights the significance of health care coverage to uptake of HIV testing in the United States. 49 HIV testing for pregnant women has been recommended by the United States Preventive Services Task Force as grade ‘A’ preventive service, and hence it is provided by most insurers without cost-sharing under the Affordable Care Act. 50…”
Section: Discussionmentioning
confidence: 99%
“…Private health insurance plans are also required to provide appropriate care to those enrolled in their plans and in most cases are more effective than public insurance [30]. Additionally, health insurance has greatly influenced HIV testing, with insurance coverage increasing HIV testing rates more so among high-risk populations [31], and containing the epidemic among those without insurance [32]. In Europe, just like the US, both public resources and private health insurance offers coverage for citizens living with HIV [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with past research suggesting that health coverage increases the rate of HIV testing (and thus the rate of diagnoses 31 ), particularly among high-risk populations. 32 Past research has suggested that marijuana use, either recreationally or in the context of sex, is an important risk factor for the transmission of both HIV and STIs among high-risk populations. 33 Other research has also shown that those who use marijuana either recreationally or as a sex-drug are less likely to be aware of their HIV-positive status 22 and more likely to participate in HIV risk behaviors, such as group sex and condomless sex, respectively.…”
Section: Discussionmentioning
confidence: 99%